Enhanced dynamo drive for the sawtooth relaxation process due to non-uniform resistivity distribution in a reversed field pinch - Wentan Yan; Ping Zhu; Hong Li; Wandong Liu; Bing Luo; Haolong Li (Nuclear Fusion)
In this work, we use the three-dimensional resistive MHD code NIMROD to investigate the impact of resistivity inhomogeneity on the sawtooth process of a cylindrical reversed field pinch (RFP) plasma. The simulation employs a non-uniform resistivity profile similar to experiments, which monotonically increases from the core to the edge as the temperature decreases. The resistivity inhomogeneity introduces an additional electric field in the plasma, which accelerates the inward diffusion of magnetic flux and changing the self sustained reversal state, hence significantly enhances the dynamo effect and the sawtooth process in the RFP plasma.